Supercooling preservation on quality of beef steak. (June 2020) - You, Youngsang; Her, Jae-Young; Shafel, Timothy; Kang, Taiyoung; Jun, Soojin
Abstract: A combination of a pulsed electric field (PEF) and oscillating magnetic field (OMF) was used to maintain a supercooled state in beef steak (London Broil) with an internal temperature of approximately −4 °C for up to 14 days. Quality factors such as color, lipid oxidation, drip loss and texture of supercooled beef samples were evaluated and compared with those of refrigerated (4 °C), two frozen (freezing at −10 °C (slow freezing, SF) and −20 °C (rapid freezing, RF)), and fresh samples. In 14 days of storage, there were no significant differences in color parameter values between supercooled and fresh beef samples ( P > 0.05). The Thiobarbituric acid reactive substances (TBARS) of supercooled samples after 14 days of storage were significantly lower than those of refrigerated and SF samples ( P < 0.05). The cell damage was visualized through optical micrographs. While the drip loss and tenderization due to intracellular ice formation occurred with SF beef, these physical changes were not observed in supercooled beef during the storage. Highlights: The applied PEF and OMF protocols successfully preserved beefsteaks at −4 °C without ice nucleation. The 14 day supercooled beef samples could maintain their original freshness factors. The supercooled beef samples could extend the shelf life of beef samples without any freezing damage.